Management of operation poles of steam power plant by using cpfd-based technology to analyze the characteristics of fuel fluidisation in cfb type boilers - Wardoyo, Johan Hadi (Institute of Computer Science (IOCS), 2024)
This study aims to analyze fluid flow and particle motion characteristics in the combustion chamber of the Circulating Fluidized Bed (CFB) Boiler at PLTU Labuhan Angin using Computational Particle Fluid Dynamic (CPFD) technology. Operational data collection methods and quantitative approaches are used in this study. Operational data from the CFB Boiler of PLTU Labuhan Angin is obtained from the control room and instruments installed in the CFB Boiler. In addition, data on coal feeding, bed particles, material properties of bed particles, and detailed drawings of the CFB boiler were also collected. The data is used as input to perform modeling simulations using CPFD. CPFD was used to predict the fluid flow and particle motion in the combustion chamber, temperature distribution, and the dominant area affected by erosion. The results show that CPFD technology can be used to analyze the characteristics of fluid flow and particle motion in the combustion chamber of a CFB Boiler. In addition, the results of this study can contribute to the development of electrical energy technology. It is expected that the results of this study can provide a deeper understanding of the management of PLTU operating patterns using CPFD technology